Prolapsed ileocolic intussusception in an infant: An uncommon presentation - Jamil M. Suleiman; David Msuya; Murad Tarmohamed; Jay Lodhia (Elsevier, 2021)
Intussusception is a common pediatric emergency, although a prolapsed intussusception is a rare entity, often misdiagnosed as a rectal prolapse.We report a 10-month-old female baby who presented with a three week history of a mass protruding per anus and vomiting, and a 2 week history of bloody diarrhoea. A clinical diagnosis of a prolapsed intussusception was made and no imaging studies were ordered to avoid a delay in management. The patient underwent an emergency laparotomy, where a dual reduction was done and the bowels were found to be ischemic hence a right hemicolectomy was performed with end-to-end ileo-transverse anastomosis. Unfortunately, 2 weeks post laparotomy, the patient presented with a high output enterocutaneous fistula. Another emergency laparotomy was performed, with findings of intestinal adhesions and an anastomotic leak. Adhesiolysis was done along with re-freshening of the ileo-transverse anastomosis.Intussusceptions presenting in the form of a prolapse through the anus is a rare condition indicating a serious sign and is often mistaken for a rectal prolapse. A digital rectal examination can help differentiate the two from each other. Surgery is the mainstay treatment for a prolapse intussusception, and should not be delayed.